2013
DOI: 10.3126/kumj.v10i2.7341
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Emergency Management of Avulsed Teeth Among General Dentists in Kathmandu

Abstract: BackgroundAn avulsed permanent tooth is one of the most emergency situations in dentistry. Dentists handling the situation should have adequate knowledge in this field. ObjectiveTo assess the level of knowledge of emergency management of avulsed teeth among general dentists in Kathmandu. MethodsA questionnaire containing 10 close ended questions about emergency management of avulsed teeth was distributed among 102 general dental practitioners working in different private dental hospitals and clinics of Kathman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 17 publications
0
24
0
3
Order By: Relevance
“…The guidelines of International Association for Dental Traumatology (IADT) and American Academy of Pediatric Dentistry (AAPD) emphasized on the immediate re-implantation of an avulsed tooth 1,9 also it was reported that immediate re-implantation of lost teeth is the treatment of choice for avulsed teeth. 14,15 International Association for Dental Traumatology (IADT) 1 recommended that not all avulsed teeth should be re-implanted as in sever caries or periodontal diseases, un-cooperative children and sever medical conditions (cardiac or immune-compromised patients) in the present study more than two-third of the student agreed not to implant all avulsed teeth. Approximately half of study group knew the ideal time for re-implantation of avulsed tooth which was 15 minutes this finding is in constance with the finding of Limbu et al study 55% 12 that time is also recommended by IADT.…”
Section: Discussionmentioning
confidence: 72%
“…The guidelines of International Association for Dental Traumatology (IADT) and American Academy of Pediatric Dentistry (AAPD) emphasized on the immediate re-implantation of an avulsed tooth 1,9 also it was reported that immediate re-implantation of lost teeth is the treatment of choice for avulsed teeth. 14,15 International Association for Dental Traumatology (IADT) 1 recommended that not all avulsed teeth should be re-implanted as in sever caries or periodontal diseases, un-cooperative children and sever medical conditions (cardiac or immune-compromised patients) in the present study more than two-third of the student agreed not to implant all avulsed teeth. Approximately half of study group knew the ideal time for re-implantation of avulsed tooth which was 15 minutes this finding is in constance with the finding of Limbu et al study 55% 12 that time is also recommended by IADT.…”
Section: Discussionmentioning
confidence: 72%
“…As respostas obtidas neste estudo sugerem uma condição preocupante, principalmente em virtude de a pesquisa ter sido realizada com profissionais da rede municipal de saúde, os quais muitas vezes são os responsáveis pelo atendimento de urgência dos pacientes com esse tipo de trauma. Tais resultados são similares aos de alguns estudos feitos com o mesmo propósito, evidenciando que mesmo em diferentes regiões pesquisadas há falha no conhecimento sobre trauma dentário [9,13,16]. Isso pode ter relação com o fato de que não são todos os cursos de graduação que incluem o tema trauma dentário na grade curricular, sendo o assunto geralmente restrito a cursos de pósgraduação.…”
Section: Discussionunclassified
“…Some of these studies are limited to solely avulsion cases [25,[36][37][38][39]. However, the concept of trauma encompasses a wide range of clinical conditions starting from a simple concussion, progressing towards more complex cases such as complicated crown fractures, crown-root fractures, intrusions, extrusions and alveolar injuries.…”
Section: Discussionmentioning
confidence: 99%